Procedural fairness and interfirm cooperation in strategic alliances - Luo, Yadong (Strategic Management Journal, 2008)
Abstract This study applies the justice theory to address interpartner cooperation in strategic alliances. It emphasizes how procedural fairness as perceived by boundary spanners in these alliances influences cooperation outcomes. We theorize that procedural fairness improves cooperation results through enhancing relational value and curtailing relational risk in an environment characterized by both economic and social exchange. Our path analysis suggests that procedural fairness has a direct effect on operational outcome, but an indirect effect on financial outcome via increased trust driven by fairness. Procedural fairness contributes more to performance outcomes when strategic alliances are equity joint ventures than if they are contractual agreements. Theoretical and managerial implications arising from the findings are highlighted. Copyright © 2007 John Wiley & Sons, Ltd.